PEMBUATAN DESAIN KARAKTER ANIMASI 2D â€œTERJEBAK HOAKSâ€ DALAM BENTUK VEKTOR - Umi Kalsum Nasution; Muchamad Fajri Amirul Nasrullah; Sandi Prasetyaningsih; Anis Rahmi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2023)
Traditional 2D animation is time-consuming and costly, but technological developments have brought innovations in 2D animation creation through digitization. Vector-based 2D animation uses computer software and utilizes vector-based images to produce smooth animation. The advantages of vector-based 2D animation are the flexibility in character changes and editing, as well as the ability to reuse vector images that have already been created. This saves animation production time and costs and speeds up the production process through rigging and tweening techniques. The character design production process of the 2D animation "Terjebak Hoaks" uses Christopher Jones' design process method and applies the basic concept, size, and variation of Tom Bancroft's character design method. Each character has a different shape, size, and pose, reflecting different characteristics. The final results of this research are three 2D animated character designs in vector form that will become characters and mediums in driving the plot of the animated story "Terjebak Hoaks".